Insertion trauma of a novel inner ear catheter for intracochlear drug delivery - Gerlitz, Matthias; Yildiz, Erdem; Gadenstaetter, Anselm J.; Niisuke, Katrin; Kandathil, Sam A.; Nieratschker, Michael; Landegger, Lukas D.; Honeder, Clemens; Arnoldner, Christoph (Frontiers in Veterinary Science, 2024)
Introduction Even with recent research advances, effective delivery of a compound to its target cells inside the inner ear remains a challenging endeavor due to anatomical and physiological barriers. Direct intracochlear drug administration with an inner ear catheter (IEC) aims to overcome this obstacle and strives to provide a safe and efficient way for inner ear pharmacotherapy. The goal of this study was to histologically and audiologically evaluate the traumatic properties of a novel IEC for intracochlear drug delivery in a large animal model. Methods Seven inner ears of piglets that had undergone intracochlear fluorescein isothiocyanate dextran application via an IEC (n = 4) or round window membrane (RWM) puncture with a needle (n = 3) followed by sequential apical perilymph sampling were histologically analyzed. Additionally, obtained objective auditory compound action potential and cochlear microphonic measurements were compared. Cochlear cryosections were stained using hematoxylin and eosin, and preservation of inner ear structures was investigated. Moreover, one cochlea was methylmethacrylate-embedded and analyzed with the IEC in situ. Results Histological evaluation revealed an atraumatic insertion and subsequent compound application in a majority of IEC-inserted inner ears. Click cochlear compound action potential (CAP) shifts in the IEC groups reached a maximum of 5 dB (1.25 ± 2.5 dB) post administration and prior to perilymph sampling. In comparison, application by RWM puncture generated a maximum click CAP hearing threshold shift of 50 dB (23.3 ± 23.1 dB) coinciding with coagulated blood in the basal cochlear turn in one specimen of the latter group. Furthermore, in situ histology showed an atraumatic insertion of the IEC demonstrating preserved intracochlear structures. Conclusion The IEC appears to be a promising and efficient way for inner ear drug delivery. The similarities between the porcine and human inner ear enhance the clinical translation of our findings and increase confidence regarding the safe applicability of the IEC in human subjects.